2009
DOI: 10.1590/s0104-66322009000100021
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of a rotating packed bed distillation column

Abstract: -The purpose of this work was to study the mass transfer performance of rotating packed beds applying the "Higee" process. The operations were carried out with the n-hexane/n-heptane distilling system at atmospheric pressure and under total reflux conditions. The rotating speed could be varied between 300 and 2500 rpm, which provided centrifugal forces from 5 to 316 times the Earth's gravity. The effects of concentration, vapor velocity, rotating speed and packing type (two different Raschig ring sizes and str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 11 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…RPB can be classified into 2 types, countercurrent flow and cross flow, depending on the flow directions of gas and liquid. RPB has been used to many unit operations such as N] 28.6 ± 1.2 39.6 ± 1.4 60.5 ± 1.5 Cadena et al, 2004 absorption (Munjal et al, 1989a, b;Cheng and Tan, 2006;Tan and Chen, 2006;Jassim et al, 2007;Cheng and Tan, 2009;Cheng and Tan, 2010, Cheng and Tan, 2011, desorption (Keyvani and Gardner, 1989;Liu, 2006, 2007), dehydration (Flowler, 1989), volatile organic compounds (VOCs) absorption (Singh et al, 1992;Hsu and Lin, 2011), seawater deaeration (Peel et al, 1998), synthesis of nanoparticles (Chen et al, 2000;Wang et al, 2004), distillation (Lin et al, 2002;Nascimento et al, 2009), ozonation Ku et al, 2008;Chang et al, 2009b). Munjal et al (1989a, b) showed a significant improvement of the gas-liquid mass transfer for CO 2 capture using an aqueous solution containing 0.5 to 1.0 N of NaOH.…”
Section: Higee Technologymentioning
confidence: 99%
“…RPB can be classified into 2 types, countercurrent flow and cross flow, depending on the flow directions of gas and liquid. RPB has been used to many unit operations such as N] 28.6 ± 1.2 39.6 ± 1.4 60.5 ± 1.5 Cadena et al, 2004 absorption (Munjal et al, 1989a, b;Cheng and Tan, 2006;Tan and Chen, 2006;Jassim et al, 2007;Cheng and Tan, 2009;Cheng and Tan, 2010, Cheng and Tan, 2011, desorption (Keyvani and Gardner, 1989;Liu, 2006, 2007), dehydration (Flowler, 1989), volatile organic compounds (VOCs) absorption (Singh et al, 1992;Hsu and Lin, 2011), seawater deaeration (Peel et al, 1998), synthesis of nanoparticles (Chen et al, 2000;Wang et al, 2004), distillation (Lin et al, 2002;Nascimento et al, 2009), ozonation Ku et al, 2008;Chang et al, 2009b). Munjal et al (1989a, b) showed a significant improvement of the gas-liquid mass transfer for CO 2 capture using an aqueous solution containing 0.5 to 1.0 N of NaOH.…”
Section: Higee Technologymentioning
confidence: 99%
“…Therefore, the gas-liquid mass transfer would frequently be enhanced by a factor of 10-100 and the dramatic reduction in the equipment volume would be achieved, thereby reducing the capital and operating costs [5]. A variety of studies have appeared in which the attention was focused on the applications of the countercurrent-flow RPB in diverse processes such as distillation [6][7][8][9][10][11], absorption [12][13][14][15][16][17][18][19][20][21][22][23][24][25], stripping [26][27][28][29][30], deaeration [31][32][33][34][35], reactive precipitation [36][37][38][39][40][41][42][43][44][45][46][47], and ozone oxidation [48][49][50][51]…”
Section: Introductionmentioning
confidence: 99%
“…However, the incomplete or no specification of the liquid distributor and/or the packings in many HiGee studies, added to the aforementioned low superficial velocities offsets the usefulness of the mass transfer data reported and makes it difficult to fairly compare different HiGee configurations. For instance, the K G a data reported by Nascimento et al 66 is several orders of magnitude higher than the data reported by Ramshaw and Mallinson. 1 Since the former does not report gas flows, it is not possible to explain this difference based on gas Reynolds numbers.…”
Section: Other Higee Equipmentmentioning
confidence: 58%